Understanding co-polymerization in amyloid formation by direct observation of mixed oligomers. Issue 7 (19th May 2017) - Young, Lydia M.; Tu, Ling-Hsien; Raleigh, Daniel P.; Ashcroft, Alison E.; Radford, Sheena E.
Abstract : Co-assembly into hetero-oligomers controls the lag time of amylin assembly by a mechanism reminiscent of prions. Abstract : Although amyloid assembly in vitro is commonly investigated using single protein sequences, fibril formation in vivo can be more heterogeneous, involving co-assembly of proteins of different length, sequence and/or post-translational modifications. Emerging evidence suggests that co-polymerization can alter the rate and/or mechanism of aggregation and can contribute to pathogenicity. Electrospray ionization-ion mobility spectrometry-mass spectrometry (ESI-IMS-MS) is uniquely suited to the study of these heterogeneous ensembles. Here, ESI-IMS-MS combined with analysis of fibrillation rates using thioflavin T (ThT) fluorescence, is used to track the course of aggregation of variants of islet-amyloid polypeptide (IAPP) in isolation and in pairwise mixtures. We identify a sub-population of extended monomers as the key precursors of amyloid assembly, and reveal that the fastest aggregating sequence in peptide mixtures determines the lag time of fibrillation, despite being unable to cross-seed polymerization. The results demonstrate that co-polymerization of IAPP sequences radically alters the rate of amyloid assembly by altering the conformational properties of the mixed oligomers that form.